AB1396 Teaching the millennials: using youtube for teaching rheumatology in the standard educational settings. (12th June 2018) - El Miedany, Y.; El Aroussy, N.; Youssef, S.; Almedany, S.; Palmer, D.
Abstract : Objectives: To assess learning potential and educational value of online videos made freely available via a dedicated YouTube channel for undergraduate and post-graduate students studying musculoskeletal medicine. Methods: The YouTube video database was systematically searched using 5 search terms related to "Joint": examination, anatomy, regional anatomy, OSCE and Ultrasonography. Two independent clinical reviewers assessed videos for procedural technique and educational value using a 5-point global score, ranging from 1=poor quality to 5=excellent educational quality. To be included in the teaching process the clip must score ≥4. Permission for sharing the video was sought from the publisher. 59 undergraduate 55 postgraduate trainees were included in this educational activity. The students were sent the YouTube channel link to the students for viewing prior to the class-time active learning session. The teaching session adopted an interactive learning environment and the course instructor served as a facilitator rather than a dominator and offered timely feedback/guidance to students. Evaluation of the teaching session was assessed using a scenario based learning and an evaluation check list. The students were asked to complete a survey based on a 5-point Likert scale: to assess for their perceived effectiveness and satisfaction. The outcomes of the evaluation sheet and students' survey, were compared to 55 undergraduate and 52 postgraduate trainees, a control group, who were taught in former years on the same topics in a lecture-based model using the standard teaching protocols. Results: 25 videos met the inclusion criteria and were considered useful for teaching purposes. The average length was 5.31±2.28 min. The mean global score for educational value was 4.3±0.3. There was no significant difference regarding socio-demographics between the 2 students' groups included in this work. In the study group 93% of the students viewed the videos prior to the class session, and 95% attended the education sessions in comparison to 86% attendance in the traditional teaching group. Students reported an increase in knowledge, a positive learning experiences and perceptions of the online teaching model. Student perceived effectiveness and satisfaction was significantly high among the online flipped learning in contrast to the traditional teaching comparative group (4.88 Vs 4.31, p<0.05). Similarly, analysis of the students' assessment scores after the scenario based learning sessions was higher in the online learning group compared to the students taught by traditional methods (p<0.01). Conclusions: Making videos on Joint anatomy and OSCE joint examination freely available on a dedicated channel on the YouTube appeared to be suitable and valuable for medical students, fellows, and residents learning. YouTube is a great example for web-based modern musculoskeletal teaching tailored to the students' needs/time, and this educational approach seems to be very well received by the students. However, though the learning potential of the internet is incredible, finding the best content can be a challenge. Acknowledgements: Omar El Miedany for setting up the YouTube channel Disclosure of Interest: None declared